Impact of Severe Salt Stress on Morphological, Physiological, and Biochemical Parameters in Alfalfa (Medicago sativa L.) - Nassira Srhiouar; Mohamed Ferioun; Said Bouhraoua; Khalil Hammani; Said Louahlia (Environmental Sciences Proceedings, 2022)
In the Mediterranean area, climate change induces an important increase in soil salinity, which threatens crop production. Here, we aimed to test the impact of severe salt stress on the Alfalfa (Medicago sativa L.) used by Moroccan breeders. Stress was applied by increasing salinity gradually by 8 dS/m. Two weeks later, the root dry weight (RDW) and shoot dry weight (SDW) were measured as morphological parameters. Soluble proteins, total soluble sugars (TSS), and proline contents were quantified in both of leaves and roots parts. Furthermore, Chlorophyll a (Chl a), b (Chl b), and total Chlorophyll (Chl T) contents were quantified in leaves to estimate the salt stress impact on the photosynthetic apparatus. Our results showed a significant decrease in morphological parameters under stress. Additionally, a significant reduction in photosynthetic pigment was recorded. Compared to leaves, important accumulations of proline and soluble protein contents in roots were observed. These results indicate that under salt treatment, alfalfa plants react to salinity by storing many molecules in the roots for planned mobilization after recovery.